Foxo4‐ and Stat3‐dependent IL‐10 production by progranulin in regulatory T cells restrains inflammatory arthritis. Issue 4 (23rd December 2016) - Fu, Wenyu; Hu, Wenhuo; Shi, Lei; Mundra, Jyoti Joshi; Xiao, GuoZhi; Dustin, Michael L.; Liu, Chuan‐ju
Abstract : Progranulin (PGRN) restrains inflammation and is therapeutic against inflammatory arthritis; however, the underlying immunological mechanism remains unknown. In this study, we demonstrated that anti‐inflammatory cytokine IL‐10 was a critical mediator for PGRN‐mediated anti‐inflammation in collagen‐induced arthritis by using PGRN and IL‐10 genetically modified mouse models. IL‐10 green fluorescent protein reporter mice revealed that regulatory T (Treg ) cells were the predominant source of IL‐10 in response to PGRN. In addition, PGRN‐mediated expansion and activation of Treg cells, as well as IL‐10 production, depends on JNK signaling, but not on known PGRN‐activated ERK and PI3K pathways. Furthermore, microarray and chromatin immunoprecipitation sequencing screens led to the discovery of forkhead box protein O4 and signal transducer and activator of transcription 3 as the transcription factors required for PGRN induction of IL‐10 in Treg cells. These findings define a previously unrecognized signaling pathway that underlies IL‐10 production by PGRN in Treg cells and present new insights into the mechanisms by which PGRN resolves inflammation in inflammatory conditions and autoimmune diseases, particularly inflammatory arthritis. —Fu, W., Hu, W., Shi, L., Mundra, J. J. Xiao, G., Dustin, M. L., Liu, C. Foxo4‐ and Stat3‐dependent IL‐10 production by progranulin in regulatory T cells restrains inflammatory arthritis. FASEB J . 31, 1354–1367 (2017) www.fasebj.org